Prospects for observation at CERN in NA62. (July 2015) - Hahn, F; Rinella, G Aglieri; Aliberti, R; Ambrosino, F; Angelucci, B; Antonelli, A; Anzivino, G; Arcidiacono, R; Azhinenko, I; Balev, S; Bendotti, J; Biagioni, A; et al.
Abstract: The rare decays are excellent processes to probe the Standard Model and indirectly search for new physics complementary to the direct LHC searches. The NA62 experiment at CERN SPS aims to collect and analyse O (10 13 ) kaon decays before the CERN long-shutdown 2 (in 2018). This will allow to measure the branching ratio to a level of 10% accuracy. The experimental apparatus has been commissioned during a first run in autumn 2014.